Fraseologia i discurs narratiu: anàlisi d'alguns casos en la novel·lística contemporània - Piquer, Adolf (Caplletra. Revista Internacional de Filologia, 1995)
Phraseology provides many resources in the construction of narratives: marking the story progress, settling registers, etc. This paper deals mainly with examples taken from contemporary Catalan novel.